Dissemination of Cordyceps fumosorosea by entomopathogenic Nematodes - Hopfgartner, Miriam (Jihočeská univerzita, 2022)
C. fumosorosea is an entomopathogenic fungus that has been used as a biocontrol agent against various insect hosts for some time. Its efficacy as an entomopathogen can be increased by joined application of the fungus with entomopathogenic nematodes. The aims of this thesis are to investigate the impact of the foraging strategy of different nematode species on the spore dispersal of C. fumosorosea and the significance the nematode's 2nd stage cuticle holds for spore dissemination. Additionally, novel approaches for the enhancement of spore transmission in soil environments via adhesives are explored.
Dissemination of Cordyceps fumosorosea by entomopathogenic Nematodes
Keywords: entomopathogenic nematodes; steinernema feltiae; steinernema carpocapsae; heterorhabditis bacteriophora; entomopathogenic fungi; cordyceps fumosorosea; conidia; blastospores; spore dispersal; adhesives; PDA plates; soil substrates; galleria mellonella; entomopathogenic nematodes; steinernema feltiae; steinernema carpocapsae; heterorhabditis bacteriophora; entomopathogenic fungi; cordyceps fumosorosea; conidia; blastospores; spore dispersal; adhesives; PDA plates; soil substrates; galleria mellonella